The Influence of Heuristics on Investment Decision Making in Cryptocurrency Assets (A Study of Retail Investors in the Bandung Raya Area) - Mulyadi , Rangga Dhimas Radithya; Lastari , Hidya Indira; Chaniago , Harmon (RISK : Jurnal Riset Bisnis dan Ekonomi, 2025)
In recent years, the cryptocurrency market in Indonesia has grown rapidly. Along with this trend, investor behavior is frequently influenced by cognitive shortcuts known as heuristics. The purpose of this study is to look at how heuristic biases such as representativeness, overconfidence, anchoring, availability bias, and the gambler's fallacy affect retail investment decisions in the Bandung Raya area. A quantitative approach with a survey method was used to collect data from 139 respondents, which were then analyzed using statistical techniques such as correlation tests and simple linear regression. The findings show that heuristic biases have a significant impact on investment decisions, emphasizing the significance of raising investor awareness of psychological factors that may interfere with rational judgment when making cryptocurrency investments.